Kajian Biblika Tentang Hidup Kudus Berdasarkan Imamat 20:1-27 - Florence Farida; Debora Debora (Jurnal Teologi Praktika, 2025)
This study aims to uncover biblical truth concerning holy living based on Leviticus 20:1–27. The method employed is hermeneutics, utilizing principles of textual and contextual exegesis. This research analyzes the teaching of holy living as presented in Leviticus 20:1–27, including the standards of holiness, actions that violate holiness, principles of holy living, and the importance of living a holy life. The results of the exegetical analysis indicate that holy living involves separating oneself from what is unclean and consecrating one’s life to God, encompassing both one’s way of life and all aspects of existence that are set apart from worldly elements that may defile holiness. In the context of the nation of Israel at that time, they were set apart from the surrounding nations to become a holy people, distinct from others, so that the holiness of God would be reflected through their worship and lifestyle.